Implications of Public Understanding of COVID-19 in Saudi Arabia for Fostering Effective Communication Through Awareness Framework - Alanezi, Fahad; Aljahdali, Anan; Alyousef, Seham; Alrashed, Hebah; Alshaikh, Wyam; Mushcab, Hayat; Alanzi, Turki (Frontiers in Public Health, 2020)
Background: Participation of public is considered to be an important and most effective approach for controlling the spread of novel coronavirus and limiting the impact of COVID-19. However, considering its novel nature, it is very much essential to create awareness among the public in taking preventive measures with timely and accurate updates through verified sources. However, misinformation and myths continued to spread in online communities, which have resulted in serious damages. Objective: Focusing on these aspects, this paper reviews the public awareness about COVID-19, myths surrounding it, its symptoms, treatment, transmission, importance of information sources, types of information to be considered in awareness campaigns, promotional channels, and their implications in Saudi Arabia. Methods: An online questionnaire-based survey was used for collecting data related to five major aspects related to COVID-19 and awareness creation process. The survey was accessed by 1881 people, out of which 741 people participated in the survey. However, 150 dropouts were identified who left the survey in between, as a result of which a final sample of 591 was achieved, indicating the response rate of 39.3% (741/1881), and a completion rate of 79.76%. Results: Awareness levels related to COVID-19, its means of transmission, preventive measures, symptoms, and treatment of the participants were identified to be moderate to high (60%-80%). However, reliance on few myths, and violation of certain preventive measures such as staying at were identified with majority of the participants (more than 60%). Ministry of Health was identified to be most reliable source of information followed by family and friends. 15 types of information, identified to be highly relevant and important which need to be effectively disseminated among the public through effective communication channels. Conclusions: Lack of awareness can result in serious outcomes in relation to COVID-19. Effective awareness campaigns including relevant information from reliable sources can improve the knowledge of people, and they must be effective in developing positive